Exploring Polycarpa aurata Quoy and Gaimard, 1834 Extracts as Antibiotic Candidates: GC-MS Profiling and Molecular Docking Study - Sardiani, Nenis; Litaay, Magdalena; Dwyana, Zaraswati; Wardhani, Riuh (HAYATI Journal of Biosciences, 2025)
Marine natural products have garnered global interest due to their remarkable bioactive compounds. The tunicate P. aurata, a highly abundant marine invertebrate, possesses significant bioactive potential with applications as an anti-cancer, antibacterial, and antifungal agent. This study aims to evaluate the potential of P. aurata bioactive compounds as antibiotic candidates through in vitro testing and to explore their activity via an in-silico approach using molecular docking. P. aurata was extracted using maceration, yielding both methanol and n-hexane extracts. The methanol extract of P. aurata demonstrated greater efficacy than the n-hexane extract, particularly against Staphylococcus aureus with an inhibition zone diameter of 18.8 mm, compared to 13 mm for Salmonella typhi, both at a 25% concentration. In comparison, the positive control, ciprofloxacin, produced an inhibition zone ranging from 22 to 24 mm for both bacterial strains. GC-MS analysis of the extract revealed three compounds with high % area and similarity index values: Cyclohexane, 1,3,5-triphenyl, Cholesta-5,22-dien-3-ol, and Cholesta-3,5-diene, all of which were suitable for the selected protein target. Computational analysis through molecular docking demonstrated that these compounds exhibit stronger binding affinities compared to ciprofloxacin. This study suggests that the extract of P. aurata is a promising source of bioactive compounds with substantial therapeutic potential as an antibacterial and antibiotic candidate.